Implementation of demand system restrictions and accuracy of QUAIDS model estimator on animal food demand in Indonesia - Iriany, Atiek; Sui, Jeky; Anindita, Ratya; Khoiriyah, Nikmatul; Sa’diyah, Ana (Eastern-European Journal of Enterprise Technologies, 2022)
Demonstration on restrictions and accuracy of an estimator is pivotal since the incomplete restrictions will make the estimator inaccurate that they cannot be used for the need of decision making. In this study, the demand system’s three primary requirements-adding up, homogeneity, and symmetry ‒ are examined. This current research was intended to demonstrate restrictions and accuracy of Quadratic Almost Ideal Demand System (QUAIDS) model estimator. The source of the data was referred to the results of National Socio-Economic Survey of Indonesia in 2016, involving 291,414 households in total. Iterated Nonlinear Seemingly Unrelated Regression method was used for the estimation procedure. Parameter estimation is used to calculate the elasticity of animal protein. The results have indicated that the three restrictions of the QUAIDS model estimator, i. e. adding up, homogeneity, and symmetry, have been completed. Further, the estimation made by the QUAIDS model is valid and efficient; therefore, the estimation is potentially used as a means of calculating own and cross price elasticity, either Marshallian or Hicksian. In addition, some other parameters, such as price, income, and income squared, are also employed to calculate income elasticity. The findings show that demand is elastic for all animal proteins, except for eggs, which are inelastic. Beef is most elastic. According to the income elasticity results, all animal proteins are considered luxury foods in Indonesia, except for eggs, which have an income elasticity of less than one. To fulfill Indonesian households’ needs for animal protein, the income policy is more suited for beef, while the price strategy is more effective for animal proteins including chicken, milk, fresh fish, and eggs